Deep Brain Stimulation Response in Pathologically Confirmed Cases of Multiple System Atrophy - Ullman, Michael (2011)
Deep brain stimulation is a treatment for select cases of medication refractory movement disorders including Parkinson’s disease. Deep brain stimulation has not been recommended for treatment in multiple system atrophy patients. However, the paucity of literature documenting the effects of deep brain stimulation in multiple system atrophy patients and the revelation of a levodopa-responsive subtype of multiple system atrophy suggests further investigation is necessary. This study summarizes the positive and negative effects of deep brain stimulation treatment in two pathologically confirmed multiple system atrophy patients from the University of Florida Deep Brain Stimulation-Brain Tissue Network. Clinical diagnosis for the two patient cases did not match the neuropathological diagnosis. We noted that in both pathologically confirmed multiple system atrophy patients, death occurred as a result of myocardial infarction. Importantly, there was reported transient benefit in levodopa responsive features that indicate deep brain stimulation may be an option for select multiple system atrophy patients.